2019
DOI: 10.1186/s41824-019-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Ability of artificial intelligence to diagnose coronary artery stenosis using hybrid images of coronary computed tomography angiography and myocardial perfusion SPECT

Abstract: Background Detecting culprit coronary arteries in patients with ischemia using only myocardial perfusion single-photon emission computed tomography (SPECT) can be challenging. This study aimed to improve the detection of culprit regions using an artificial neural network (ANN) to analyze hybrid images of coronary computed tomography angiography (CCTA) and myocardial perfusion SPECT. Methods This study enrolled 59 patients with stable coronary artery disease (CAD) who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Visual assessment of SPECT heart perfusion images faces several challenges, including the lack of reproducibility due to the intra-observer and interobserver variability, dependency on nuclear medicine expert or radiologist experience, and increased time and cost of the interpretation process. Machine learning and Deep learning techniques exhibited promising potential for the detection and classi cation of coronary artery disease from SPECT MPI images compared with other approaches, including human observer diagnosis and quantitative analysis of perfusion defects [4,6,[9][10][11][12][13][14][15][18][19][20][21]. A comparison to the related studies is listed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Visual assessment of SPECT heart perfusion images faces several challenges, including the lack of reproducibility due to the intra-observer and interobserver variability, dependency on nuclear medicine expert or radiologist experience, and increased time and cost of the interpretation process. Machine learning and Deep learning techniques exhibited promising potential for the detection and classi cation of coronary artery disease from SPECT MPI images compared with other approaches, including human observer diagnosis and quantitative analysis of perfusion defects [4,6,[9][10][11][12][13][14][15][18][19][20][21]. A comparison to the related studies is listed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kang et al developed a ML algorithm that identified coronary stenosis of 25% or more with an accuracy of 94% compared to visual identification of lesions with stenosis by expert readers using consensus reading (46). Yoneyama et al developed a neural network for the detection of coronary stenoses from CTA images that cause perfusion defects on single-photon emission CT, achieving comparable results with physician experts (47). Several studies have reported neural networks that automatically grade CAD severity from CTA images according to the Coronary Artery Disease Reporting and Data System (CAD-RADS) (48)(49)(50)(51), with satisfactory results (46,47,50).…”
Section: Automated Plaque Detection and Coronary Artery Calcium Calcu...mentioning
confidence: 99%
“…Yoneyama et al evaluated the possibility to identify the grading of coronary stenosis and its impact in terms of ischemia using a cohort of patients who underwent CCTA and perfusion single photon emission computed tomography (SPECT) [ 37 ]. The authors focused on the application of an artificial neural network (ANN) with hybrid imaging obtained by the combination of CCTA and myocardial perfusion SPECT [ 37 ]. Using this algorithm, the specificity, sensitivity, and accuracy to identify coronary artery stenosis >70% were 31%, 78%, and 67%, respectively [ 37 ].…”
Section: Ai Application For the Evaluation Of Coronary Artery Stenmentioning
confidence: 99%
“…The authors focused on the application of an artificial neural network (ANN) with hybrid imaging obtained by the combination of CCTA and myocardial perfusion SPECT [ 37 ]. Using this algorithm, the specificity, sensitivity, and accuracy to identify coronary artery stenosis >70% were 31%, 78%, and 67%, respectively [ 37 ].…”
Section: Ai Application For the Evaluation Of Coronary Artery Stenmentioning
confidence: 99%